أثر برنامج تدريبي مكثف للمحاجة التعاونية على اكتساب الاتجاهات الإيجابية نحو تعلم مهارات المحاجة لدي طلاب الجامعة - أبو النيل، هبة الله محمود (الجمعية المصرية للدراسات النفسية, 2017)
تهدف الدراسة الراهنة فحص أثر التدريب على تحسن الاتجاهات نحو مهارات المحاجاة لدى طلاب الجامعة واكتساب الاتجاهات الإيجابية نحو تعلمها وأجريت الدراسة على 73 مبحوثا من الجنسين، من طلاب وطالبات جامعة بني سويف، الملتحقين بكليات الطب البشري والعلوم والآداب والتجارة والحقوق، منهم (33) شكلوا المجموعة التجريبية ((10) من الذكور و(23) من الإناث)، بمتوسط عمر (19.9 سنة) ± 3.37، و(40) شكلوا المجموعة الضابطة ((9) من الذكور و(31) من الإناث بمتوسط عمر (19.7 سنة) ±3.16)، وطبق على المجموعة التجريبية برنامجا تدريبيا للمحاجة التعاونية يعتمد على تيسير المناقشات بين عدد من المشاركين، كشكل من أشكال التفكير التعاوني ويتضمن استراتيجيات المحاجاة التعاونية من قبيل تشجيع الطلاب على الاستدلال وإبراز وتوضيح عمليات التفكير لديهم من خلال التفكير بصوت عال وتشجيع الطلاب على المواجهة بالأفكار المضادة والاعتراف بالمنطق السليم؛ وتلخيص ما يطرحه باقي أطراف المحاجة بالإضافة لاستخدام مفردات ومهارات التفكير الناقد وأظهرت النتائج أن الأداء البعدي للعينة التجريبية كان أفضل من الأداء القبلي بشكل دال، كما أظهرت الفروق أن أداء العينة التجريبية كان أفضل من أداء العينة الضابطة بشكل دال أيضا وذلك على مستوى مدى استخدام الأفراد لمهارات المحاجة واتجاهاتهم نحو تلك المهارات وعلى اكتساب الاتجاهات الإيجابية نحو البرنامج.
The current study aims to examine the effect of training on improving attitudes towards argumentation skills among university students and gaining positive attitudes towards learning these skills. The study was conducted on 73 male and female students studying both humanties and sciences from the University of Beni Suef (The students belonged to faculties of medicine, science, arts, commerce and law) The experimental group constituted of (33) students (10 males and 23 females), with an average age (19.9 years) +3.37. (40) students formed the control group (9 males and 31 females with an average age (19.7 years) +3.16). The experimental group participated in a training program for collaborative argumentaion. The program constituted in facilitating discussions among multiple participants as a form of collaborative Strategies for collaborative argumentation included training argumentation, students in making inferences and deductions; clarifying their reasoning processes while thinking aloud with others; countering an argument and accepting the other’s consistent logic; and summarizing the points presented by other parties of the argument using the vocabulary and skills of critical thinking (Jonassen & Kim 2010). Results showed that tire post-test performance of the experimental sample was better than its pre-test performance regarding their ability to use skills of collaborative argumentation and their positive attitude towards these skills. Moreover, differences showed that the performance of the experimental sample was better than the control sample both in the use by individuals of acquired skills of collaborative argumentation and in the individuals’ positive attitude towards those skills.
Keywords: علم النفس التربوي -- طلبة الجامعات -- الإستراتيجيات التعليمية